Thymoquinone and Pyruvate Metabolism in Cancer-Associated Fibroblasts: Emerging Therapeutic Insights - Khalid, Jabir Padathpeedika; Martin, Taniya Mary; Kishore Kumar, Meenakshi Sundaram; Sukumaran, Suma (Asian Pacific Journal of Cancer Biology, 2026)
Overview: Cancer continues to be a major global health burden, with GLOBOCAN 2020 reporting 19.3 million new cases and 10 million deaths. Despite advances in treatment, aggressive cancers especially liver and pancreatic remain difficult to manage. Lifestyle factors such as smoking, alcohol use, obesity, and infections contribute significantly to the rising incidence. Conventional therapies often face limitations due to resistance and late-stage progression. Increasing research now focuses on metabolic vulnerabilities within the tumor microenvironment, particularly the role of cancer-associated fibroblasts (CAFs). Driven by signals like TGF-β, PDGF, and IL-6, CAFs fuel tumor growth through metabolic reprogramming and the Reverse Warburg effect. Pyruvate, a central metabolite in glycolysis, plays a key role in these energy-driven processes. Methods: A structured search of PubMed and Google Scholar was performed using the keywords cancer, pyruvate pathways, Thymoquinone, Nigella sativa, and cancer-associated fibroblasts. Studies addressing TQ’s anticancer and metabolic effects were reviewed. Results: Thymoquinone (TQ), the main bioactive constituent of Nigella sativa, possesses antioxidant, anti-inflammatory, and antiproliferative actions. Evidence shows that TQ can influence glycolysis, mitochondrial activity, lactate production, and redox balance. However, studies specifically exploring its effects on pyruvate metabolism in CAFs remain limited. Early observations suggest that TQ may interfere with CAF-mediated metabolic support to tumors. Conclusion: This review highlights the potential of TQ in targeting cancer metabolism, particularly pyruvate-related pathways in cancer cells and CAFs. Further focused research may help translate these insights into effective metabolic-based therapeutic strategies.